Aspartate Rescues S-phase Arrest Caused by Suppression of Glutamine Utilization in KRas-driven Cancer Cells - Patel, Deven (J Biol Chem, 2016)
During G(1)-phase of the cell cycle, normal cells respond first to growth factors that indicate that it is appropriate to divide and then later in G(1) to the presence of nutrients that indicate sufficient raw material to generate two daughter cells. Dividing cells rely on the “conditionally essential” amino acid glutamine (Q) as an anaplerotic carbon source for TCA cycle intermediates and as a nitrogen source for nucleotide biosynthesis. We previously reported that while non-transformed cells arrest in the latter portion of G(1) upon Q deprivation, mutant KRas-driven cancer cells bypass the G(1) checkpoint, and instead, arrest in S-phase. In this study, we report that the arrest of KRas-driven cancer cells in S-phase upon Q deprivation is due to the lack of deoxynucleotides needed for DNA synthesis. The lack of deoxynucleotides causes replicative stress leading to activation of the ataxia telangiectasia and Rad3-related protein (ATR)-mediated DNA damage pathway, which arrests cells in S-phase. The key metabolite generated from Q utilization was aspartate, which is generated from a transaminase reaction whereby Q-derived glutamate is converted to α-ketoglutarate with the concomitant conversion of oxaloacetate to aspartate. Aspartate is a critical metabolite for both purine and pyrimidine nucleotide biosynthesis. This study identifies the molecular basis for the S-phase arrest caused by Q deprivation in KRas-driven cancer cells that arrest in S-phase in response to Q deprivation. Given that arresting cells in S-phase sensitizes cells to apoptotic insult, this study suggests novel therapeutic approaches to KRas-driven cancers.